Distribution of neuropeptide Y-like immunoreactivity and its relationship to FMRF-amide-like immunoreactivity in the sixth lumbar and first sacral spinal cord segments of the rat - Sasek, CA (J Neurosci, 1985)
The present study was aimed at describing the distribution of neuropeptide Y (NPY)-like immunoreactivity in the sixth lumbar (L6) and first sacral segments (S1) of the rat spinal cord, comparing this distribution to that of FMRF-amide-like immunoreactivity and determining whether NPY- and FMRF-amide-like immunoreactivities are present in the same neurons in the dorsal gray commissure (DGC) in L6 and S1 of the rat spinal cord. For distribution studies tissue from colchicine-treated animals was processed according to the peroxidase- antiperoxidase technique using anti-NPY as the primary antiserum. For co-localization studies serial 5-micron sections were processed for immunofluorescence. Adjacent sections were incubated with either anti- NPY or anti-FMRF-amide as the primary antiserum. The number of immunoreactive cells per section was counted and each section was photographed. The sections were then restained with the other antiserum (i.e., tissue first stained with anti-NPY was stained with anti-FMRF- amide and vice versa), the number of cells per section was recounted, and the sections were rephotographed. NPY-like immunoreactive cells and fibers were identified in the DGC, sacral parasympathetic nucleus, substantia gelatinosa, marginal zone, nucleus proprius, and ventral horn. Every cell in the DGC that contained NPY-like immunoreactivity was found also to contain FMRF-amide-like immunoreactivity, and the distribution of NPY-like immunoreactive fibers was found to be similar, although denser than FMRF-amide-like immunoreactive fibers. The distribution of NPY-like immunoreactivity in L6 and S1 of the rat spinal cord suggests that an NPY-like peptide may be involved in regulation of pelvic viscera, processing of primary afferent information, and motor regulation of pelvic muscles. The presence of NPY- and FMRF-amide-like immunoreactivities in the same neurons in the DGC together with the lack of bona fide FMRF-amide in the rat central nervous system, the presence of NPY in the rat central nervous system, and the cross-reactivity of anti-FMRF-amide with NPY support the hypothesis that the FMRF-amide antiserum recognizes an NPY-like peptide in the rat spinal cord.